Effects of dietary canthaxanthin on growth and body colour of blood parrot cichlid Amphilophus citrinellus × Paraneetroplus synspilus - Li, M.; Rahman, Mohammad Mustafizur; Wu, Biao; Lin, Y. C. (Springer, 2017)
A 6-week experiment was carried out to evaluate the effects of diets containing 0, 0.004, 0.008, 0.012 and 0.016 % synthetic canthaxanthin on growth, feed utilization and skin pigmentation of parrot cichlid (Amphilophus citrinellus × Paraneetroplus synspilus). Three hundred and sixty fish with initial body weights of 18.0 ± 1.6 g were randomly stocked equally into 15 glass aquaria (each 80 9 40 9 50 cm3) to form five triplicate groups. Fish were fed one of five diets daily at 2 % of their total body weight. At the end of the experiment, all fish were harvested and weighed to calculate growth parameters. After weighing, randomly selected two fish from each aquarium were used to assess the body colour using a colorimeter. Results indicated that dietary canthaxanthin supplementation had no effect on growth, feed conversion ratio, ingestion rate and condition factor of parrot cichlid. The degree of pigmentation in skin of parrot cichlid increased significantly (P\0.05) with increasing inclusion of canthaxanthin up to 0.012 % in the diet. Canthaxanthin inclusion over that level did not lead to increase more redness, yellowness, hue and chroma of parrot cichlid skin. Diet containing more than 0.012 % canthaxanthin even decreased redness of fish skin (16 % decreased) compared to diet containing 0.012 % canthaxanthin (18.67 ± 0.32). In the present study, observations based on the effects of various canthaxanthin levels on colour parameters suggest that the diet containing a 0.012 % canthaxanthin may be considered as the best level of canthaxanthin supplementation for best skin colouration of parrot cichlid.